Systematized co-creation? Danish municipalities use of temporary committees - Kjær, Ulrik; Op, Niels; Kjærgaard Thomsen, Mette (Politica, 2021)
One-way Danish municipalities try to facilitate co-creation processes is by establishing the type of committees made possible by the municipal statute section 17, subsection 4. These 17-4 committees do not have formal decision-making power but can be established ad hoc, include member from outside the municipal council, and often seek to work across traditional sector boundaries. For a 17-4 committee to have potential to facilitate co-creation, two criteria must be met: 1) focus must be on developing new policies and solutions, and 2) the committee must include external members from outside the council or municipal administration. A survey among all 98 Danish municipalities shows that eight out of ten municipalities have established one or more 17-4 committees. Most include external members, and many of them focus on developing new policies. In total, two out of three of the committees live up to the above-mentioned criteria. From the viewpoint of the municipalities, the committees help make political decisions more responsive to citizens’ needs and wishes and infuse the political decision-making processes with new knowledge.